Research Advances on CD47 Molecules in Tumor Microenvironment of Diffuse Large B-cell Lymphoma - LIU Yiyue; SU Yanyu; LYU Geng; XU Zizhen (Zhongliu Fangzhi Yanjiu, 2023)
Diffuse large B-cell lymphoma (DLBCL) is a common, highly aggressive and heterogeneous hematologic malignancy in adults. Patients with DLBCL have substantially differences in molecular biological characteristics, clinical manifestations, and prognosis. Increasing evidence shows that the tumor microenvironment plays an important role in the occurrence and development of DLBCL. CD47, an integrin related protein, is overexpressed in DLBCL cells and plays a key role in immune escape of lymphoma. This work reviews the research progress of CD47 in DLBCL TME in terms of CD47-related signal pathway, CD47 role in DLBCL TME, and therapeutic strategies targeting CD47 in DLBCL TME.